Pengaruh Metode Fonik dengan Media Flash Card dalam Meningkatkan Kemampuan Membaca Siswa - Moh Taufiq; Choirus Sholihin (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
The research conducted at SDN Sidotopo I Surabaya aims to find out whether there is an effect of the phonics method using Flash Card Media on improving students' reading skills. The background for conducting this research was to depart from the reading ability of grade I students which was still very low, the lack of variation in the methods and learning media used for reading lessons which resulted in students not being interested in learning to read. This study uses a quantitative experimental model method, with two classes; class IA which has 28 students as an experimental class that applies the phonics method with Flash Card media and IB totaling 28 students as the control class does not apply the phonics method with this media. The results of the research hypothesis testing conducted in the experimental class and control class, obtained Tcount is 2.1969 and Ttable is 2.0040 so the results of Tcount > Ttable (2.1969 > 2.0040) which means H1 is accepted and H0 is rejected. So it can be concluded that there is an influence of the phonics method with flash card media on improving students' reading skills at SDN Sidotopo I Surabaya